Measuring Energy Security : Trends in the Diversification of Oil and Natural Gas Supplies - Loungani, Prakash (IMF Working Papers; Working Paper, 2011)
We present evidence on one facet of energy security in OECD economies - the extent of diversification in sources of oil and natural gas supplies. Viewed from the perspective of the energy-importing countries as a whole, there has not been much change in diversification in oil supplies over the last decade, but diversification in sources of natural gas supplies has increased steadily. We document the cross-country heterogeneity in the extent of diversification. We also show how the extent of diversification changes if account is taken of the political risk attached to suppliers; the size of the importing country; and transportation risk.